2020
DOI: 10.1021/acs.energyfuels.0c02698
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Optimal Ignition Strategy of Internal Combustion Engines via Various Spark Discharge Conditions

Abstract: Spark discharge ignition can be effectively enhanced by increasing the plasma volume and its duration, but evaluation and realization of an optimal ignition performance under engine working conditions are big challenges due to the complex in-cylinder flow field and thermodynamic environment. In this investigation, ignition strategies with various spark discharge parameters were tested, and their effects on the initial flame kernel formation and propagation in the early stage of combustion were compared and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Hydrogen possesses many characteristics that significantly differ from those of traditional fossil fuels, and the conclusions of existing studies on hydrocarbon fuel engines may not necessarily apply to hydrogen. , Hydrogen has the potential to significantly enhance the brake thermal efficiency of engines because of its high energy density, low ignition energy, and broad flammability limit. Currently, hydrogen internal combustion engines can be classified into two types based on mixture formation: port fuel injection (PFI) and direct injection (DI). Tang et al conducted research on the Ford P2000 hydrogen internal combustion engine and found that although the maximum power output of the engine decreased by 35 to 50% compared to gasoline engines, lean burn reduced heat losses and improved the engine’s thermal efficiency to some extent. White et al conducted an in-depth study on the performance of PFI hydrogen internal combustion engines, and the results showed that under conditions where φ (equivalence ratio) was less than or equal to 0.5, the engine reduced NOx emissions to below 100 ppm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen possesses many characteristics that significantly differ from those of traditional fossil fuels, and the conclusions of existing studies on hydrocarbon fuel engines may not necessarily apply to hydrogen. , Hydrogen has the potential to significantly enhance the brake thermal efficiency of engines because of its high energy density, low ignition energy, and broad flammability limit. Currently, hydrogen internal combustion engines can be classified into two types based on mixture formation: port fuel injection (PFI) and direct injection (DI). Tang et al conducted research on the Ford P2000 hydrogen internal combustion engine and found that although the maximum power output of the engine decreased by 35 to 50% compared to gasoline engines, lean burn reduced heat losses and improved the engine’s thermal efficiency to some extent. White et al conducted an in-depth study on the performance of PFI hydrogen internal combustion engines, and the results showed that under conditions where φ (equivalence ratio) was less than or equal to 0.5, the engine reduced NOx emissions to below 100 ppm.…”
Section: Introductionmentioning
confidence: 99%
“… 11 14 Currently, hydrogen internal combustion engines can be classified into two types based on mixture formation: port fuel injection (PFI) and direct injection (DI). 15 20 Tang et al 21 conducted research on the Ford P2000 hydrogen internal combustion engine and found that although the maximum power output of the engine decreased by 35 to 50% compared to gasoline engines, lean burn reduced heat losses and improved the engine’s thermal efficiency to some extent. White et al 22 conducted an in-depth study on the performance of PFI hydrogen internal combustion engines, and the results showed that under conditions where φ (equivalence ratio) was less than or equal to 0.5, the engine reduced NOx emissions to below 100 ppm.…”
Section: Introductionmentioning
confidence: 99%